Learning and Transfer of Graphomotor Skills in Three 7- to 10-Year-Old Children with Developmental Coordination Disorder: Case Reports. - Josseron, Laureen; Clerc, Jérôme; Jolly, Caroline (Children, 2025)
Highlights: What are the main findings? The acquisition of graphomotor abilities is not systematically impaired in children with DCD. Graphomotor acquisition depends on the presence and severity of associated dysgraphia. Transfer of learning is preserved in children with DCD, whatever the severity of the disorder, and even in the presence of dysgraphia. What is the implication of the main finding? Better understanding of the acquisition of fine motor activities and transfer of learning in children with singular DCD. Background/Objectives: Children with Developmental Coordination Disorder (DCD) frequently experience handwriting difficulties, or dysgraphia. The association between DCD and dysgraphia has long been observed and described. However, few studies have examined the acquisition and transfer of graphomotor skills in these children, i.e., their ability to learn new graphic gestures and reuse them in new tasks. The objective of this study was to evaluate the acquisition of pseudo-letters and their transfer to different types of tasks in children with DCD. Methods: Three case studies of children with DCD, with or without an associated dysgraphia, were compared to an age-matched control group. Participants learned to produce six pseudo-letters during an acquisition phase, then transferred their learning to two tasks: the first assessed the transfer of learned strokes to new pseudo-letters, and the second assessed the transfer of stroke sequences to combinations of two or three pseudo-letters. Performances were analyzed on the basis of four variables: handwritten product quality, and three measures reflecting the handwriting process, i.e., velocity, fluency, and the number of stops during writing. Results: Acquisition and transfer abilities differed depending on the presence and severity of dysgraphia. Only the presence of a severe dysgraphia associated with DCD led to a lower quality and a greater on-paper velocity than typically developing children during the learning test. As to transfer, DCD children were able to transfer their learning, even in the presence of a dysgraphia. Only in the case of the second, more distant, transfer task, the presence of a severe dysgraphia led to an increase in velocity and in fluency, and a decrease in the number of stops, in addition to the lower quality. This pattern is typical of handwriting in DCD children with dysgraphia. Conclusions: The acquisition of de novo graphomotor skills depends on the presence and severity of a dysgraphia associated with DCD, but not on the severity of other motor impairments. The further transfer of these skills is preserved in DCD children.